Experiences and practices of people categorised as being ‘at risk’ based on age during the COVID-19 pandemic: a qualitative study in the UK and Germany - Susannah Mayhew; Stephanie Drössler; Katharina Wabnitz (BMJ Open)
Objectives The aim of this study was to comparatively explore the social representations of risk in individuals categorised ‘at risk’ based on age during the COVID-19 pandemic. What characterised their sense-making of being at risk and what effects did this have on their lives, behaviour and identities?Design Interview-based qualitative study.Setting UK and Germany, July–August 2020.Participants 11 individuals from Germany and eight from the UK were recruited purposively. Inclusion criteria: to be at risk for a severe course of COVID-19 due to age ≥50 years (Germany) and ≥70 years (UK) based on official communication by the respective national public health authority.Exclusion criteria: any form of dementia, pre-existing mental health issues, congenital physical or mental disabilities, being resident in a care home, having a personal relationship to the principal investigator.Methods Semistructured in-depth interviews were conducted remotely. Reflexive thematic analysis was carried out to inductively develop themes illustrative of shared patterns of meaning across the whole data set.Results Three main themes are reported. ‘Establishing safe spaces’ (perceiving safety and risk in relation to others and implementing prevention measures to maintain safe spaces); ‘Assessing and responding to risk’ (risk as danger relative to others and risk management as a responsibility of the individual) and ‘Considerations on the value of a life’ (in relation to quality of life, length of life and capacity to contribute to society). Cross cutting all of these, is the notion of relational assessment.Conclusions The experience of risk and related behaviour is contingent on the individuals’ mindset, body and the setting (geographical, political and sociocultural) one is positioned in. Negotiating identities is an inevitable process accompanying sense-making of (new) risks. Public health practice and communication could benefit from at least being informed by and at best being based on the meanings and representations of those whose health and well-being we want to ensure.